MEDANESE NOVEL: HISTORY OF LITERATURES IN MEDAN CITY (1930—1965)/ROMAN MEDAN: SEJARAH KARYA SASTRA DI KOTA MEDAN (1930—1965) - Syahri Ramadhan; Saefur Rochmat (Balai Bahasa Provinsi Bali, 2021)
AbstractThis study aims to explain the history of the Medanese novels chronologically, starting from the development of the Medanese novels in the Dutch colonialism period to the old order, and the impact of Medanese novels to people in Medan. The sources of data are Medanese novels published from 1930 to 1965. Method used in this study was historic method studied through four stages as follows: (1) heuristic (to collect sources); (2) verification of data (to test validity of data); (3) interpretation; (4) historiography (writing). The data were analyzed by diachronic approach as a method in the length of time, but limited in space. The results of this study indicated that development of Medanese novels in Dutch colony time (from 1912 to 1942) experienced speedily progressing. Medanese novels were on its peak in 1930, until the term flood of romance emerged which was marked by the number of romances published. Medanese novels could compete against novels published by Balai Pustaka, a publisher previously established by the government of the Dutch colonialism. However, at time of the Japanese occupation (from 1942 to 1945), the Medanese novels experienced decreasing, even lost from distribution, and from early independence (from 1945 to 1950) to old order (from 1950 to 1966), the Medanese novels raised again, but the existence was unlike the previous. Moreover, the Medanese novels writing had impacts on social life in Medan, such as politic, education, social, and culture. Keywords: Medanese novels, history, literature, Medan AbstrakPenelitian ini bertujuan untuk menjelaskan sejarah perkembangan roman Medan secara kronologis, yang dimulai dari perkembangan roman Medan pada masa kolonial Belanda hingga orde lama, serta dampak penulisan roman Medan bagi masyarakat kota Medan. Sumber data penelitian ini adalah roman Medan terbitan tahun 1930—1965. Metode yang digunakan dalam penelitian ini, yaitu metode sejarah yang dikaji melalui empat tahapan, meliputi (1) heuristik (pengumpulan sumber); (2) verifikasi data (menguji keabsahan sumber); (3) interpretasi (penafsiran); (4) historiografi (penulisan). Adapun analisis data menggunakan pendekatan diakronis yang merupakan suatu pendekatan yang memanjang dalam waktu, tetapi secara ruang terbatas. Hasil dari penelitian ini menunjukkan bahwa perkembangan roman Medan pada masa kolonial Belanda (1912—1942) mengalami kemajuan yang begitu pesat. Roman Medan berada di puncak kejayaannya pada tahun 1930 hingga muncul istilah banjir roman yang ditandai dengan banyaknya roman yang terbit. Secara kuantitas roman Medan mampu bersaing dengan roman terbitan Balai Pustaka yang merupakan penerbit buku yang telah didirikan terlebih dahulu oleh pemerintah Belanda. Akan tetapi, pada masa pendudukan Jepang (1942—1945) roman Medan mengalami kemunduran bahkan hilang dari peredaran, dan pada masa awal kemerdekaan (1945—1950) hingga masa Orde Lama (1950—1966), roman Medan bangkit kembali, tetapi eksistensinya tidak seperti dahulu. Selain itu, penulisan roman Medan ini memiliki dampak terhadap kehidupan masyarakat Medan di antaranya dalam bidang politik, pendidikan, sosial, dan budaya. Kata kunci: roman Medan, sejarah, karya sastra, Medan